Impulse Noise: Can Hitting a Softball Harm Your Hearing? - Korrine Cook; Samuel R. Atcherson (The Scientific World Journal)
The purpose of this study is to identify whether or not different materials of softball bats (wooden, aluminum, and composite) are a potential risk harm to hearing when batting players strike a 12′′ core .40 softball during slow, underhand pitch typical of recreational games. Peak sound pressure level measurements and spectral analyses were conducted for three controlled softball pitches to a batting participant using each of the different bat materials in an unused outdoor playing field with regulation distances between the pitcher’s mound and batter’s box. The results revealed that highest recorded peak sound pressure level was recorded from the aluminum (124.6 dBC) bat followed by the composite (121.2 dBC) and wooden (120.0 dBC) bats. Spectral analysis revealed composite and wooden bats with similar broadly distributed amplitude-frequency response. The aluminum bat also produced a broadly distributed amplitude-frequency response, but there were also two very distinct peaks at around 1700 Hz and 2260 Hz above the noise floor that produced its ringing (or ping) sound after being struck. Impulse (transient) sounds less than 140 dBC may permit multiple exposures, and softball bats used in a recreational slow pitch may pose little to no risk to hearing.